Insulin glargine/lixisenatide fixed‐ratio combination (iGlarLixi) compared with premix or addition of meal‐time insulin to basal insulin in people with type 2 diabetes: A systematic review and Bayesian network meta‐analysis. Issue 11 (3rd September 2020) - Home, Philip; Blonde, Lawrence; Kalra, Sanjay; Ji, Linong; Guyot, Patricia; Brulle‐Wohlhueter, Claire; Murray, Erin; Shah, Roshan; Sayre, Toby; Shaunik, Alka
Abstract: Aim: To assess the efficacy and safety of iGlarLixi, a fixed‐ratio combination of insulin glargine 100 U/mL and lixisenatide, relative to premix insulin and other insulin options through network meta‐analysis. Methods: A systematic literature search identified randomized controlled trials (RCTs) comparing iGlarLixi, premix insulin or basal insulin (BI) in combination with meal‐time insulin, in people inadequately controlled with BI. Eligible RCTs were compared using Bayesian network meta‐analysis. Results: Eight RCTs, some open‐label, involving 3538 participants, with a study duration of 24‐30 weeks were included. The estimated difference in HbA1c reduction with iGlarLixi compared with premix insulin was −0.50%‐units (95% credible interval: −0.93 to −0.06) with 98% probability of iGlarLixi being superior to premix. Estimates for iGlarLixi versus meal‐time + BI (thrice‐daily meal‐time insulin + basal) and basal‐plus (once‐daily meal‐time insulin + BI) were −0.35 (−0.89 to +0.13)%‐units and −0.68 (−1.18 to −0.17)%‐units with probabilities of real difference of 94% and 99%, respectively. Safety outcome analysis suggested that iGlarLixi had lower rates of both confirmed and documented symptomatic hypoglycaemia compared with premix insulin (probabilities of 85% and 93%, respectively) and lower weight gain (probability 98%). Conclusions: iGlarLixi showed similar or improved efficacy and safety versus other intensification choices from BI included in this study, providing a clinically relevant treatment option in people with type 2 diabetes not well controlled on BI.